MYTHOLOGY IN SULALATUS SALATIN: A MORAL RESPONSIBILITY IN FULFULLING THE KING’S VISION - Nor Anita Binti Mat Isa; Norazimah Binti Zakaria (International Journal of Malay-Nusantara Studies, 2018)
The Sulalatus Salatin is clearly a form of historical literature that contained a lot of stories, myth, especially during the period pre-Melaka until the existence of Melaka itself.The objective of this study is to identify the mythological aspect and its kinship with the king’s authority. The research will use cultural theories. Mythology has always been connected with the tales of gods which always have a kinship with the constituents of faith.This element usually associated with the beginning of a race or ancestral root of an individual, especially royalties which were invariably tied to the extraordinary & peculiar tales.In the essence, mythology is the tale of the origins which encompasses the roots of blood line, the name of a place, the arrival of Islam, etc. In the context of societal belief, mythology is not just something respectable, but the mythical event was thought to actually took place and studied as something sacred.This clearly proves that myth has already existed even before the emergence of Tun Seri Lanang as the author of Sulalatus Salatin. Therefore, this research is produced with the aim to observe the mythological elements in the text of Sulalatus Salatin and the role of its story as a moral duty in fulfilling the King’s wishes.